Erlotinib induced fatal interstitial lung disease in a patient with metastatic non-small cell lung cancer: case report and review of literature - Ankit Mangla; Nikki Agarwal; Chou Carmel; Thomas Lad (Rare Tumors, 2016)
Erlotinib is one of the most widely used tyrosine kinase inhibitor targeting human epidermal growth factor receptor. Since its introduction, it has revolutionized the treatment of advanced non-small cell lung cancer. Skin rashes and diarrhea are the most often reported side effects of erlotinib however it is also associated with interstitial pneumonitis or interstitial lung disease, which often turns out to be fatal complication of using this medicine. Though reported scarcely in the western world, the association of interstitial lung disease with epidermal growth factor receptor has attracted a lot of attention in the recent times. Various researches working with murine models of bleomycin-induced pulmonary fibrosis have found a pro and con role of the receptor in development of the interstitial lung disease. We present the case of a patient diagnosed with stage IV adenocarcinoma of the lung with metastasis to brain. He was found to be positive for the human epidermal growth factor mutation and was hence started on erlotinib. Within a few weeks of starting the medicine the patient was admitted with diarrhea. During the course of this admission he developed acute shortness of breath diagnosed as interstitial pneumonitis. The purpose of this case report is to review the literature associated with erlotinib induced interstitial pneumonitis and make the practicing oncologists aware of this rare yet fatal complication of erlotinib. Here we will also review literature, pertaining to the role of epidermal growth factor receptor in development of interstitial lung disease.